Numerical simulations of the aspherical collapse of laser and acoustically generated bubbles - Tsiglifis, Kostas; Pelekasis, Nikos A. (Ultrasonics sonochemistry, 2007)
The details of nonlinear axisymmetric oscillations and collapse of bubbles subject to large internal or external pressure disturbances, are studied via a boundary integral method. Weak viscous effects on the liquid side are accounted for by integrating the equations of motion across the boundary layer that is formed adjacent to the interface. Simulations of single-cavitation bubble luminescence (SCBL) and single-bubble sonoluminescence (SBSL) are performed under conditions similar to reported experimental observations, aiming at capturing the details of bubble collapse. It is shown that any small initial deviation from sphericity, modeled through a small initial elongation along the axis of symmetry, may result in the formation and impact of two counter-propagating jets during collapse of the bubble, provided the amplitude of the initial disturbance is large enough and the viscosity of the surrounding fluid is small enough. Comparison between simulations and experimental observations show that this is the case for bubbles induced via a nano-second laser pulse (SCBL) during a luminescence event. In a similar fashion, simulations show that loss of sphericity accompanied with jet formation and impact during collapse is also possible with acoustically trapped bubbles in a standing pressure wave (SBSL), due to the many afterbounces of the bubble during its collapse phase. In both cases jet impact occurs as a result of P 2 growth in the form of an afterbounce instability. When the sound amplitude is decreased or liquid viscosity is increased the intensity of the afterbounce is decreased and jet impact is suppressed. When the sound amplitude is increased jet formation is superceded by Rayleigh–Taylor instability. In the same context stable luminescence is quenched in experimental observations. In both SCBL and SBSL simulations the severity of jet impact during collapse is quite large, and its local nature quite distinct. This attests to the fact that it is an energy focusing mechanism whose importance in generating the conditions under which a luminescence event is observed should be further investigated.